STUDI PERBANDINGAN KUALITAS ORGANOLEPTIK DAGING BABI BALI DENGAN DAGING BABI LANDRACE - I W. E. E., Suandana; Sriyani, N. L. P.; Hartawan, M (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
This study aims to determine differences in the organoleptic quality of balinese pork with landrace pork, This research was conducted in Slaughter House Traditional andthen in Livestock Product Technology Laboratory and Microbiology, Faculty of Animal Husbandry Universitas Udayana for two months. The study design is completely randomized design (CRD) with a ratio 2 samples of meat that has been fried and 38 semi-trained panelists. The results showed preference level panelist on the color and texture of landrace pork significantly (P<0,05) higher than balinese pork, while the preference level panelist on the aroma, flavor and overall acceptance of bali pork significantly (P<0,05) higher than the landrace pork. Based on the results of this study concluded that the panelists preferred the organoleptic of balinese pork compared with landra ce pork.This research was conducted in Slaughter House Traditional andthen in Livestock Product Technology Laboratory and Microbiology, Faculty of Animal Husbandry Universitas Udayana for two months. The study design is completely randomized design (CRD) with a ratio 2 samples of meat that has been fried and 38 semi-trained panelists. The results showed preference level panelist on the color and texture of landrace pork significantly (P<0,05) higher than balinese pork, while the preference level panelist on the aroma, flavor and overall acceptance of bali pork significantly (P<0,05) higher than the landrace pork. Based on the results of this study concluded that the panelists preferred the organoleptic of balinese pork compared with landrace pork
Keywords: organoleptic, pork, balinese pig, landrace pig